Aerosols and Bacteria From Hand Washing and Drying in Indoor Air - Gião, Maria Salomé; Vardoulakis, Sotiris (Frontiers in Public Health, 2022)
Effective hand drying is an important part of hand hygiene that can reduce the risk of infectious disease transmission through cross-contamination of surfaces by wet hands. However, hand drying methods may also cause aerosolisation of pathogenic microorganisms if they are present in washed hands. This study investigated experimentally the impact of washing hands and different hand drying methods on the concentration and size distribution of aerosols and bacteria in indoor air. In this experiment, aerosol and bacteria concentrations were measured in indoor air while volunteers rinsed their hands with water or washed with soap and water prior to drying them with paper towels or jet air dryers. Results showed that the concentration of aerosols and bacteria in air increased with people walking in the room and washing hands, with a further increase during the hand drying process. The concentration of aerosols decreased with particle size, with maximum concentrations after drying hands of 6.63x106 ± 6.49 x105 and 2.28x104 ± 9.72 x103 particles m-3 for sizes 0.3 to <0.5 and ≥5.0 m, respectively. The concentration of bacteria in indoor air after drying hands increased to a maximum of 3.81x102 ± 1.48 x102 CFU m-3 (jet air dryers) and 4.50x102 ± 4.35 x101 CFU m-3 (paper towels). This study indicates that the increase of aerosols and bacteria in air after drying hands with jet air dryers or paper towels are comparable and not statistically different from concentrations associated with walking and washing hands in the same environment. This work can support the development of hand hygiene practices and guidelines for public washrooms.